2013
DOI: 10.1155/2013/529173
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Low-Frequency Magnetic Fields on Cardiomyocytes from Ischemia Reperfusion InjuryviaROS and NO/ONOO

Abstract: Background. Cardiac ischemia reperfusion (I/R) injury is associated with overproduction of reactive oxygen species (ROS). Low frequency pulse magnetic fields (LFMFs) have been reported to decrease ROS generation in endothelial cells. Whether LFMFs could assert protective effects on myocardial from I/R injury via ROS regulation remains unclear. Methods. To simulate in vivo cardiac I/R injury, neonatal rat cardiomyocytes were subjected to hypoxia reoxygenation (H/R) with or without exposure to LFMFs. Cell viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Also, Ca 2+ overload due to NMDA receptor activation induce increased H 2 O 2 production in complex I, III and II (41). The lack of a vasodilatory effect of NO in our study could be the consequence of conversion of NO and O 2 − to peroxynitrite, which is one of free radicals with most potent deleterious effect and could mediate the adverse effects of NMDA stimulation by glycine and glutamate (42,43).…”
Section: Discussionmentioning
confidence: 55%
“…Also, Ca 2+ overload due to NMDA receptor activation induce increased H 2 O 2 production in complex I, III and II (41). The lack of a vasodilatory effect of NO in our study could be the consequence of conversion of NO and O 2 − to peroxynitrite, which is one of free radicals with most potent deleterious effect and could mediate the adverse effects of NMDA stimulation by glycine and glutamate (42,43).…”
Section: Discussionmentioning
confidence: 55%
“…The study of the effects of LF-EMF on the cardiovascular system demonstrated protection against myocardial infarction (MI) [ 7 ]. Similarly, data from Ma and colleagues [ 8 ] suggest that LF-EMFs inhibit the generation of reactive oxygen species, such as nitric oxide and peroxynitrite, thereby protecting cardiomyocytes from I/R and oxidative damage. The protective effects of LF-EMF are further supported by a study examining the effects of LF-EMF on skin wound healing which suggests that LF-EMF stimulates endogenous antioxidant systems.…”
Section: Introductionmentioning
confidence: 91%
“…2 A number of studies have indicated that myocardial apoptosis is initiated shortly after the onset of ischemia; the process becomes evidently enhanced during reperfusion, which is strongly associated with heart failure. [6][7][8] ROS is a major factor generated at reperfusion that activates multiple molecular cascades of apoptosis. 4 Previous studies have revealed that oxidative stress has an important function in I/R-induced cardiomyocyte apoptosis.…”
Section: Introductionmentioning
confidence: 99%